Controversy as a Developmental Tool in Cross Self-Confrontation Analysis - Kostulski, Katia; Kloetzer, Laure (Outlines. Critical Practice Studies, 2014)
In Psychology, the issue of language usage as a means of action in psychological life requires that we question the relations between the forms of language expression and their psychological functions. The current paper contributes to an understanding of this question. The relation between form and function is examined here, with particular focus on a discursive and dialogic method employed in the Activity Clinic approach to elicit controversy as a means of developing dialogical thinking. We argue that the interfunctionality of levels of dialogue serves developmental processes, promoting thought and the possibilities for its elaboration. We describe these developmental processes on the basis of an empirical analysis of a sequence from an intervention conducted with Roman Catholic Priests on preaching in homily. Our methodological frameworks have the function of vivifying dialogical thinking about work, by making use of the interfunctionality of levels of dialogue and the vital function of social relations in the psychological life of the subjects.